Konsep Pendidikan Karakter Anak dalam Keluarga Disorot dari Surat Apostolik “Amoris Laetitia” - Kwirinus, Dismas (Vocat : Jurnal Pendidikan Katolik, 2022)
The focus of this research examines the concept of character education of children in the family highlighted from the apostolic letter of Amoris Laetitia. The topic of the study related to character education contained in "Amoris Laetitia" would be very helpful for families in educating children to have more character and be more humane. The researcher uses descriptive qualitative methods and critical reading of the text, namely: (1) Apostolic Letter "Amoris Laetitia" art. 274-279; (2) books related to children's character education; (3) Articles that concentrate on the study of Catholic religious education and the character of children. The findings in this study that character education is a form of human activity in which there is an action that educates and is intended for the next generation. Character education aims to form self-improvement in order to lead to a better life.